Analysis Performance of the Kamun Weir Irrigation Area in the Lutung Barat Canal, Majalengka Regency - Nurdiyanto, Nurdiyanto (Jurnal Improsci, 2023)
Irrigation system management aims to realize water utilization in agriculture, which is participatory, integrated, and environmentally friendly. Kamun weir is located in Liangjulang village, Kadipaten sub-district, Majalengka District, and belongs to the Kamun irrigation area. The research entitled Analysis Performance of the Kamun Weir Irrigation Area in the Lutung Barat Canal, Majalengka Regency, aims to provide an overview and problems solving that occur at the irrigation network level, restoring and optimizing its original function. The method analyzes rainfall data for water requirements, cropping patterns, and irrigation physical conditions. The results of the analysis show that the water needs of the Kamun Lutung Barat irrigation area have been met with the existing mainstay discharge. However, there was still a shortage in May period II, where the existing mainstay discharge of 3046 liters/second was still needed to meet the demand discharge of 3423 liters/second. However, after modifying the cropping pattern with padi-palawija-tebu, the water requirement in the second period of May became 2848 liters/s, so the required water discharge has been met with the existing mainstay discharge. Irrigation channel conditions are in the medium classification with a percentage of 67.58%, and the condition of the irrigation building is in the medium classification with a percentage of 66.88%.